Summary of: Developing professional status: an investigation into the working patterns, working relationships and vision for the future of UK clinical dental technicians - Lambert-Humble, Stephen (British dental journal, 2013)
Key Points Provides a baseline into the working practices, concerns and aspirations of a newly registered group of DCPs. Provides an in-depth understanding of the clinical dental technicians' (CDTs) attitudes to working within the confines of the current NHS contract commissioned by primary care trusts. Will allow future comparison with CDTs currently in training and working with and within the dental profession. Objective To explore patients' motivations and expectations for dental implants. Design Single-setting, qualitative interview study. Subjects, setting and method Semi-structured, telephone interviews were conducted with nine patients who had consulted a restorative dental practitioner with an interest in implantology about the possibility of replacing their missing teeth with dental implants. Outcome measure Interview transcripts were subjected to thematic analysis to identify relevant themes. Results The main theme to emerge was 'normality'. Participants expected implants to restore their oral-related quality of life to 'normal'. However, individual definitions of normality differed; some were appearance focused, while others were more concerned with functioning. Several participants who had completed implant treatment regarded their new prostheses as 'just like natural teeth'. Conclusions Patients' belief that dental implants are just like natural teeth could be cause for concern if it leads them to treat them as such, and thereby not follow the recommended specialist care they require. The findings emphasise the importance of good dental practitioner-patient communication in assessing expectations of treatment and outcomes. Further studies should explore the expectations of patients of different ages and socioeconomic backgrounds and consider ways of eliciting patients' beliefs about implants before treatment takes place.